Polymorphic variants at NDUFC2, encoding a mitochondrial complex I subunit, associate with cardiac hypertrophy in human hypertension - Giovanna Gallo; Maurizio Forte; Maria Cotugno; Simona Marchitti; Rosita Stanzione; Giuliano Tocci; Franca Bianchi; Silvia Palmerio; Mariarosaria Scioli; Giacomo Frati; Sebastiano Sciarretta; Emanuele Barbato; et al. (BMC, 2023)
Abstract Background A dysfunction of NADH dehydrogenase, the mitochondrial Complex I (CI), associated with the development of left ventricular hypertrophy (LVH) in previous experimental studies. A deficiency of Ndufc2 (subunit of CI) impairs CI activity causing severe mitochondrial dysfunction. The T allele at NDUFC2/rs11237379 variant associates with reduced gene expression and impaired mitochondrial function. The present study tested the association of both NDUFC2/rs11237379 and NDUFC2/rs641836 variants with LVH in hypertensive patients. In vitro studies explored the impact of reduced Ndufc2 expression in isolated cardiomyocytes. Methods Two-hundred-forty-six subjects (147 male, 59.7%), with a mean age of 59 ± 15 years, were included for the genetic association analysis. Ndufc2 silencing was performed in both H9c2 and rat primary cardiomyocytes to explore the hypertrophy development and the underlying signaling pathway. Results The TT genotype at NDUFC2/rs11237379 associated with significantly reduced gene expression. Multivariate analysis revealed that patients carrying this genotype showed significant differences for septal thickness (p = 0.07), posterior wall thickness (p = 0.008), RWT (p = 0.021), LV mass/BSA (p = 0.03), compared to subjects carrying either CC or CT genotypes. Patients carrying the A allele at NDUFC2/rs641836 showed significant differences for septal thickness (p = 0.017), posterior wall thickness (p = 0.011), LV mass (p = 0.003), LV mass/BSA (p = 0.002) and LV mass/height2.7(p = 0.010) after adjustment for covariates. In-vitro, the Ndufc2 deficiency-dependent mitochondrial dysfunction caused cardiomyocyte hypertrophy, pointing to SIRT3-AMPK-AKT-MnSOD as a major underlying signaling pathway. Conclusions We demonstrated for the first time a significant association of NDUFC2 variants with LVH in human hypertension and highlight a key role of Ndufc2 deficiency-dependent CI mitochondrial dysfunction on increased susceptibility to cardiac hypertrophy development.